Parallel coupled bandpass filter for Wimax: article / Abdullah Tohir Abdul Aziz - Abdul Aziz, Abdullah Tohir
The paper concentrates on the design of a parallel coupled bandpass filter (PCBPF). The design is developed at the centre frequency of 5.77 GHz. The bandwidth of the filter is 9%. This type of filter is suitable to be used in the Wimax systems. The filter is implemented by using cpoxy laminate with £,.=3.0 with thickness of 0.75mm thickness.